Synthesis, characterization, DNA binding and cleavage studies, in-vitro antimicrobial, cytotoxicity assay of new manganese(III) complexes of N-functionalized macrocyclic cyclam based Schiff base ligands. (1st February 2023) - Archana, B.; Sreedaran, S.
Graphical abstract: A series of binuclear manganese(III) complexes were synthesized from the macrocyclic ligands 1, 8-[bis(3-formyl-2-hydroxy-5-methyl)benzyl]-1, 4, 8, 11-tetraazacyclotetradecane (L 1 ) and 1, 8-[bis(3-formyl-2-hydroxy-5-bromo)benzyl]-1, 4, 8, 11-tetraazacyclotetradecane (L 2 ) by a Schiff base condensation with the appropriate aliphatic or aromatic diamines, MnCl2 ·4H2 O and triethylamine. All the complexes were characterized by elemental and spectral analysis. A broad band around 600–650 nm indicates a d–d transition of the metal ion, which is characteristic of the Mn 3+ ion in a 5 or 6 coordination environment. The ESR spectrum of [Mn2 L 2b ] displays a broad band without splitting, with g = 2.12, which shows there is an antiferromagnetic interaction between the two manganese ions. An irreversible reduction in the cathodic potential region and a quasi reversible oxidation in the anodic potential region were observed for all the complexes. The kinetic activity of the binuclear manganese(III) complexes were found in the range of 2.21 × 10 −3 to 8.14 × 10 −3 min −1 . The enhanced DNA binding affinity of the complexes [Mn2 L 1c ] and [Mn2 L 1e ] is due to the existence of the electron donating CH3 group which leads to a hydrophobic interaction with the hydrophobic DNA surface. The existence of the electron withdrawing Br atom in complexes [Mn2 L 2a ] and [Mn2 L 2d ] leads to a lesser DNA binding affinity. The fluorescence quenching of the binuclear manganese(III) complexes at 620 nm (d-d transition) indicates the strong coordination of the metal ions with the N and O atoms of the ligand. The 3D fluorescence spectrum of the [Mn2 L 2d ] complex has been quenched more compared to [Mn2 L 2a ], which may be due to the planarity of aromatic system. DNA cleavage by the manganese(III) complexes begins at a low concentration (25 μM) and reaches a maximum cleavage with a successive increase in concentration (100 μM). All the complexes were screened for antimicrobial activity and cytotoxicity. Abstract: A series of binuclear manganese(III) complexes were synthesized from the macrocyclic ligands 1, 8-[bis(3-formyl-2-hydroxy-5-methyl)benzyl]-1, 4, 8, 11-tetraazacyclotetradecane (L 1 ) and 1, 8-[bis(3-formyl-2-hydroxy-5-bromo)benzyl]-1, 4, 8, 11-tetraazacyclotetradecane (L 2 ) by a Schiff base condensation with the appropriate aliphatic or aromatic diamines, MnCl2 ·4H2 O and triethylamine. All the complexes were characterized by elemental and spectral analysis. A broad band around 600–650 nm indicates a d–d transition of the metal ion, which is characteristic of the Mn 3+ ion in a 5 or 6 coordination environment. The ESR spectrum of [Mn2 L 2b ] displays a broad band without splitting, with g = 2.12, which shows there is an antiferromagnetic interaction between the two manganese ions. An irreversible reduction in the cathodic potential region and a quasi reversible oxidation in the anodic potential region were observed for all the complexes. The kinetic activity of the binuclear manganese(III) complexes were found in the range of 2.21 × 10 −3 to 8.14 × 10 −3 min −1 . The enhanced DNA binding affinity of the complexes [Mn2 L 1c ] and [Mn2 L 1e ] is due to the existence of the electron donating CH3 group which leads to a hydrophobic interaction with the hydrophobic DNA surface. The existence of the electron withdrawing Br atom in complexes [Mn2 L 2a ] and [Mn2 L 2d ] leads to a lesser DNA binding affinity. The fluorescence quenching of the binuclear manganese(III) complexes at 620 nm (d-d transition) indicates the strong coordination of the metal ions with the N and O atoms of the ligand. The 3D fluorescence spectrum of the [Mn2 L 2d ] complex has been quenched more compared to [Mn2 L 2a ], which may be due to the planarity of aromatic system. DNA cleavage by the manganese(III) complexes begins at a low concentration (25 μM) and reaches a maximum cleavage with a successive increase in concentration (100 μM). All the complexes were screened for antimicrobial activity and cytotoxicity.